Ischemic stroke with unknown onset of symptoms: current scenario and perspectives for the future - Lopes, Rônney Pinto; Gagliardi, Vivian Dias Baptista; Pacheco, Felipe Torres; Gagliardi, Rubens José (Arquivos de Neuro-Psiquiatria, 2022)
Background Stroke is a major cause of disability worldwide and a neurological emergency. Intravenous thrombolysis and mechanical thrombectomy are effective in the reperfusion of the parenchyma in distress, but the impossibility to determine the exact time of onset was an important cause of exclusion from treatment until a few years ago.Objectives To review the clinical and radiological profile of patients with unknown-onset stroke, the imaging methods to guide the reperfusion treatment, and suggest a protocol for the therapeutic approach.Methods The different imaging methods were grouped according to current evidence-based treatments.Results Most studies found no difference between the clinical and imaging characteristics of patients with wake-up stroke and known-onset stroke, suggesting that the ictus, in the first group, occurs just prior to awakening. Regarding the treatment of patients with unknown-onset stroke, four main phase-three trials stand out: WAKE-UP and EXTEND for intravenous thrombolysis, and DAWN and DEFUSE-3 for mechanical thrombectomy. The length of the therapeutic window is based on the diffusion weighted imaging–fluid-attenuated inversion recovery (DWI-FLAIR) mismatch, core-penumbra mismatch, and clinical core mismatch paradigms. The challenges to approach unknown-onset stroke involve extending the length of the time window, the reproducibility of real-world imaging modalities, and the discovery of new methods and therapies for this condition.Conclusion The advance in the possibilities for the treatment of ischemic stroke, while guided by imaging concepts, has become evident. New studies in this field are essential and needed to structure the health care services for this new scenario.
Keywords: Ischemic Stroke; Neuroimaging; Tissue Plasminogen Activator; Thrombectomy